Factors causing low pass rate in mathematics at grade seven in Kwekwe rural district - Mushakwe, Abgirl Varaidzo (Midlands State University, 2018)
The purpose of the study was to find out the factors causing low pass rate in Mathematics at Grade Seven level in Kwekwe Rural District. The study was of significance because of the noted trend of low pass rate in Mathematics from the year 2015 to 2017. The qualitative research design was used to generate data in detail. The interview and observation guides as well the document analysis were the data generating instruments used in the study. A sample of twenty students, four Grade Seven teachers and two School Administrators was purposively sampled from two schools in Kwekwe Rural District. The findings of this study revealed that teachers were qualified and experienced to guide Grade Seven students and hence teacher qualification and experience were not factors contributing to low pass rate in Mathematics. However teacher centred methods, negative attitudes of students towards Mathematics and inadequate teaching and learning materials in schools are the major contributing factors causing low pass rate in Mathematics at Grade Seven level. The researcher recommends the Ministry of Primary and Secondary education to call for regular in-service training and refresher courses in the teaching of Mathematics. The School Development Committees should arrange fund raising projects to procure teaching and learning materials in schools. Teachers should use learner centred methods to teach Mathematics. The School Administrators should supervise and guide teachers in teaching Mathematics.